Comparative Study of Aescin and Atorvastatin on Lipid Profile of Albino Wistar Rats - Shazia Parveen Channar , Kumayl Abbas Meghji , Ali Abbas Thalho , Sana Kashif , Mozna Talpur , Asim Shafique Channa (Journal of Islamic International Medical College, 2021)
Objective: To observe the effects of Aescin and Atorvastatin on the lipid profile of Albino Wistar rats. Study Design: Quasi-experimental study. Place and Duration of Study: Postgraduate research laboratory at ISRA University, Hyderabad from 6 June 2018 to 7 October 2018. Materials and Methods: Fifty albino Wistar rats were divided into five groups: Group A (Control), Group B (High-fat diet), Group C (Aescin + high-fat diet), Group D (Atorvastatin + high-fat diet), Group E (Aescin Atorvastatin + high-fat diet). Pre and post-experimental body weight and biochemical analysis was done through ANOVA on SPSS version 22. The significance level was p ≤ 0. 05. Results: Marked reduction in serum Total Cholesterol (71.36 ±10.1), Triglycerides (83 ±25.66), and Low-density lipoprotein-cholesterol (32 ± 3.76) while elevation in levels of High-density lipoprotein-cholesterol (45 ± 11.85) was observed in Group E as compared to Group B. Statistically significant difference in mean post-experimental body weight body was also observed between all study groups (p ≤ 0.05). Conclusion: Combination therapy of Aescin and Atorvastatin has significant protective effects on lipid profile when compared with individual therapy of either drug.